Reefer Referendum: Comparing Marijuana Laws Across the Globe - Chris Escobar (Washington University Global Studies Law Review, 2021)
This note will broadly examine the treatment of marijuana in four countries: Singapore, Uruguay, Italy, and the United States with brief allusions to other countries to illustrate the various degrees of legality. Treating each of these four principle countries as a case study, the underlying policies and impacts of marijuana laws around the globe shall come to light. By comparing and contrasting the various laws, policies, and approaches taken around the world, a path for the ideal method of marijuana regulation may unveil itself That overall path currently trends in the direction of medicinal legalization and decriminalization for recreational use, but should begin to head toward adding full recreational legality with regulations that standardize the end product, distribution, and consumption in a similar manner to alcohol. The analysis of the laws and policies of each country shall explore the following issues in a systematic process: first, this note answers whether or not marijuana usage is legal in a given country. Then, if marijuana usage is not legal, the extent of punishment is discussed along with the impacts of that punishment. Alternatively, if marijuana usage is legal, this note looks at the extent of a given country's regulation, including whether usage is allowed recreationally or for medicinal purposes only, the extent of taxation, the implementation of potency limits, or age restrictions. Following this analysis may illustrate why marijuana should attain legal status for both medicinal and recreational purposes, with corresponding regulations for each.